Pengembangan Aplikasi Katalog Wedding Organizer berbasis Android menggunakan Restful Web Service di Ruang Lingkup Kota Malang - Fernanda Yerisha Hartinah Ridwan; Bayu Priyambadha; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Married is activity that everyone will do someday when they grown up. Based on Badan Pusat Statistik's data on 2015 there's 1.958.394 couples who had married in Indonesia, in East Java itself, there's 313.150 couples who had married and had recorded. It's a lot of number if its compared to a number of all couples who had married in Indonesia. The marriage itself, has an aim to unite two persons in marriage vows. Theres must be a wedding ceremony to celebrate that marriage. That wedding ceremony have some kind of variant that based on the tradition, tribe, the habit and the religion of the couple. So the couple wants the wedding ceremony be the unforgetable one. In wedding ceremony, theres banquets for the guests, decorations, make up for the bride and the groom and the gifts. But, theres a lot of couples that hard to arrange their time to find the right vendor or wedding organizer that suit their wedding's theme and to arrange the wedding ceremony. Beside, information about the vendor or wedding organizer are difficult to find, because of the lack of promotion. So, that's why this research are made to develop a system to connect the vendor with the couples. There's 2 platform in this system, that are in website and mobile. For the vendor, they can access the website platform to input detail information about their bussiness. For the couple, they can access the mobile platform to search and get information about vendor. While developing this system, the researcher use the Restful Webservice method to share data between that platform, so the system can't directly access the data in database. And the system access data from API that it provided in JSON form.